(untitled) (Medico Legal Update, 2021)
This study aims to determine the effect of giving massage, physiotherapy and nutritional needs based on nutritional adequacy rates to increase endurance of leg and heart muscles in the Road Racetour De Singkarak Bicycle Racing Athlete. The sample in this study uses a total sample technique that is all athletes Pelatnas Road Racetour De Singkarak athletes, amounting to 10 people. The findings of this study include, 1) There is an effect of giving massage to increase leg and heart muscle power, with the average rating of the experimental group using the Strocking Effleurage method, traction (traction) and Effleurage more dominant than the average value of the control group. 2) There is an influence of giving physiotherapy to increase leg and heart muscle power, and the administration of control group physiotherapy with Exercise therapy technique is more dominant than the administration of Thermotherapy (Heat therapy/Heat Therapy). 3) There is an influence of nutritional needs based on the nutritional adequacy rate on the increase in leg and heart muscle power of the Road Racetour De Singkarak Road Race, with the average experimental group being more dominant than the control group